2014
DOI: 10.1556/avet.2014.016
|View full text |Cite
|
Sign up to set email alerts
|

A new operative technique for aural haematoma in dogs: A retrospective clinical study

Abstract: Aural haematoma is treated either by surgical or by conservative treatment. Both techniques usually require several interventions and re-checks. A new operation technique has been evaluated that requires only a single procedure but is as effective as the techniques used previously. The haematoma is opened, cleaned surgically and the two layers of the auricular cartilage are appositioned inside with several suture lines placed on both sides of the incision, alternating the sides approaching to the sagittal cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Aural hematomas reportedly occur more commonly in medium-to large-breed dogs, 4,9,12,13,23 pendulous-eared dogs (80% to 88% 9,11,13 ), and middleaged to older dogs (> 4 years; 86% to 93% 9,[11][12][13] ), and similar trends were observed in the present study. Golden Retrievers and Labrador Retrievers represented 43% (22/51) of the dogs in the present study, which was similar to percentages in some previous reports (32% to 67% 9,11,13 ); however, whether these breeds have a higher risk remains unknown because of a lack of comparison with the general dog population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Aural hematomas reportedly occur more commonly in medium-to large-breed dogs, 4,9,12,13,23 pendulous-eared dogs (80% to 88% 9,11,13 ), and middleaged to older dogs (> 4 years; 86% to 93% 9,[11][12][13] ), and similar trends were observed in the present study. Golden Retrievers and Labrador Retrievers represented 43% (22/51) of the dogs in the present study, which was similar to percentages in some previous reports (32% to 67% 9,11,13 ); however, whether these breeds have a higher risk remains unknown because of a lack of comparison with the general dog population.…”
Section: Discussionsupporting
confidence: 90%
“…3,11,20,21 These techniques are usually performed in conjunction with procedures intended to decrease the size of the AH cavity, such as application of compression bandages, 1,10,[18][19][20][21] placement of mattress sutures or stents in the pinna, 1,10,[19][20][21][22] ablation of the cavity with a carbon dioxide laser, 11 or placement of continuous sutures between the cavity's walls. 23 Reported recurrence rates after these surgeries are low (0% to 27%). 5,7,11,12,17,18,20,21,23 In a recent survey 22 of veterinary practitioners in the United Kingdom, LCI was the most frequently used first-line treatment for AHs.…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…In this prospective clinical study, we tested the clinical effect of L-PRP in treatment of aural hematoma based on hemostatic, anti-inflammatory and angiogenic effect of autologous L-PRP demonstrated by several previous studies in dogs [ 47 , 48 , 54 ]. Furthermore, recently, a human review to evaluate the efficacy of PRP in reducing post-operative split-thickness skin graft loss and hematoma formation showed that PRP decreased the odds of hematoma formation by 79% [ 55 ].…”
Section: Discussionmentioning
confidence: 99%